Adoecimento de professores iniciantes no exercício da docência e a surdez do sistema de ensino estadual/MT - Silveira, Ester Landvoigt da (2022)
This research approaches as main theme the professional practice of beginner teachers and deployment concerning the relation between work and health. It is inserted in the Postgraduate Program in Education of the Federal University of Mato Grosso/University Campus of Rondonópolis, currently Federal University of Rondonópolis (UFR). The research was delineated by the following interrogations: What justifies the expressive incidence of beginner teachers, appointed through the public tender of 2017, present illness conditions in the initial phase of the profession? Is there a relation between the teaching work and the illness of beginner teachers in teaching service in public schools of the state education network in Rondonópolis/MT? The objective of the research was: comprehend the context of illness in beginner/entrant teachers in the state of MT since 2017 and to what they attribute the health situation they are in. To reach the general objective, the studies sought to answer the following specific objectives: Register what teachers point out about the process of insertion and reception in the schools, when they entered them after the tender in 2017; Analyze possible relations between teaching work and illness, pointed out in the perceptions of the newly appointed teachers; Register what procedures ill teachers point out to ease the conditions that they passed through in their journey in the school. It was determined the qualitative approach and were used document analysis, studies of reference broadening on the theme and semi structured interview. The results point out that, the misinformation, the absence of interpersonal relations in the workplace and the lack of projects and programs and policies of reception, insertion and induction of beginner teachers in MT has been the biggest cause of illness among professionals.